Amnion-Derived Mesenchymal Stromal/Stem Cell Paracrine Signals Potentiate Human Liver Organoid Differentiation: Translational Implications for Liver Regeneration - Lo Nigro, Antonio; Gallo, Alessia; Bulati, Matteo; Vitale, Giampiero; Paini, Diego Sebastian; Pampalone, Mariangela; Galvagno, Daniele; Conaldi, Pier Giulio; Miceli, Vitale (Frontiers in Medicine, 2021)
The prevalence of end-stage liver diseases has reached very high levels globally and the election treatment for those patients is orthotopic liver transplantation. That procedure is very complex and, due to the limited number of suitable organ donors, considerable research has focused on alternative therapeutic options. For instance, the use of cell therapy, such as the transplantation of hepatocytes to promote liver repair/regeneration, has been explored, but standardized protocols to produce suitable human hepatocytes are still limited. On the other hand, liver progenitor and multipotent stem cells offer potential cell sources that could be used clinically. Different studies have reported therapeutic effects of transplanted mesenchymal stromal/stem cells (MSCs) on end-stage liver diseases. Moreover, it has been shown that delivery of MSC-derived conditioned medium (MSC-CM), can reduce cell death and enhance liver proliferation in fulminant hepatic failure. Therefore, it is believed that MSC-CM contains many factors that probably support liver regeneration. In our work, we used an in vitro model of human liver organoids to study if the paracrine components secreted by human amnion-derived MSCs (hAMSCs) affect liver stem/progenitor cell differentiation. In particular, we differentiated liver organoids derived from bipotent EpCAM+ human liver cells and, on that model, we tested the effects of hAMSCs secretome derived from both 2D and 3D hAMSCs cultures. Our analysis showed that CM produced by 3D hAMSCs, was able to induce an over-expression of mature hepatocyte markers such as ALB, NTCP and CYP3A4 compared with both 2D hAMSCs cultures and conventional differentiation medium (DM). These data were confirmed by the over-production of ALB protein and over-activity of CYP3A4 observed in organoids grown in 3D hAMSC-CM. Liver repair dysfunction plays a role in the development of liver diseases and, effective repair likely requires the normal functioning of liver stem/progenitor cells. Herein, we showed that hAMSC-CM produced mainly by 3D cultures had the potential to increase hepatic stem/progenitor cell differentiation, demonstrating that soluble factors secreted by those cells are potentially responsible for the reaction. This work shows a potential approach to improve liver repair/regeneration also in a transplantation setting.